A comprehensive analysis of the effect of ethanol, methane and methane-hydrogen blend on the combustion process in a PFI (port fuel injection) engine. (August 2015) - Catapano, F.; Di Iorio, S.; Magno, A.; Sementa, P.; Vaglieco, B.M.
Abstract: The energy crisis and environmental issues make the alternative fuels, both liquid and gaseous, even more attractive because of their potentiality in reducing the fuel consumption and the pollutant emissions. Ethanol is the most promising alternative liquid fuel for spark ignition engines. It has a higher octane number, which provides good anti-knock characteristics and in the possibility to work with higher compression ratios, so improving the engine efficiency. The higher heat of vaporization compared to gasoline leads to an increased power output. Moreover, the larger oxygen content provides a more complete combustion and therefore reduced emissions. Among gaseous fuels, methane is considered one of the most interesting. It has wider flammable limits and better anti-knock properties than gasoline. Moreover, it is characterized by lower CO2 emissions. On the other hand, the slow flame propagation speed and its poor lean-burn capability produce lower engine power output with respect to gasoline. The addition of a high burning velocity fuel, such as hydrogen, allows to improve the combustion process in terms of burning velocity and extend the lean operation limit. The objective of this paper is the analysis of the effect of different fuels on the engine performance and emissions. Experimental investigations were carried out in an optically accessible small single-cylinder, spark ignition four-stroke engine. It was equipped with the cylinder head of a Port Fuel Injection commercial 244 cc engine. The engine was fueled with gasoline, ethanol, methane and a blend of hydrogen in methane. Optical measurements were performed to analyze the combustion process with high spatial and temporal resolution. In particular, the optical techniques based on 2D-digital imaging were used to follow the flame propagation in the combustion chamber. UV–visible spectroscopy allows the detection of chemical markers of the combustion process such as the radicals OH* and CH*. The exhaust emissions were characterized by means of gaseous analyzers. The measurements were performed at steady state conditions. Highlights: Optical analysis of the effect of liquid/gaseous biofuels on combustion process. Ethanol combustion is less efficient at low engine speed and load. Hydrogen addition improves methane combustion process.